The consumption of psychoactive substances among French physicians: how do they perceive the creation of a dedicated healthcare system? - Jullian, Bénédicte; Deltour, Marine; Franchitto, Nicolas (Frontiers in Psychiatry, 2023)
Introduction Substance use among physicians can have negative impacts on their health, quality of life, and patient care. While Physician Health Programs (PHPs) have proven effective, many physicians with substance use disorders (SUDs) still face obstacles in seeking help. Our study explores the expectations, attitudes, and experiences of French physicians regarding the implementation of a specialized healthcare system (SHS) for addiction, and their opinions on the factors that could improve the effectiveness of such a service, with a focus on substance use disorders (SUDs). Methods We conducted a web-based survey from April 15 to July 15, 2021, which included questions about sociodemographic characteristics, substance use, and attitudes toward a specialized healthcare system (SHS) for physicians with SUDs. Results Of the 1,093 respondents (62.5% female), 921 consumed alcohol (84.2%), and 336 (36.4%) were categorized as hazardous drinkers (AUDIT-C ≥ 4 for women and ≥ 5 for men). The mean AUDIT-C score was 3.5 (±1.7 SD), with a range from 1 to 12. Factors associated with hazardous alcohol consumption included coffee consumption [OR 1.53 (1.11–2.12)], psychotropic drug use [OR 1.61 (1.14–2.26)], cannabis use [OR 2.96 (1.58–5.55)], and other drug use [OR 5.25 (1.92–14.35)]. On the other hand, having children was associated with non-hazardous alcohol consumption [OR 0.62 (0.46–0.83)]. Only 27 physicians (2.9%) had consulted a specialist in addiction medicine, while 520 (56.4%) expressed interest in such a consultation. The main barriers to accessing a dedicated consultation were denial (16.3%), physician self-medication (14.3%), fear of judgment (12.8%), and confidentiality concerns (10.2%). Conclusion A specialized consultation with trained professionals in a neutral location can improve access to care for healthcare workers and maintain patient confidentiality and anonymity. Prevention and awareness can reduce addiction stigma and help peers in need. The improvement of healthcare workers’ addiction culture and detection of addictive behavior in peers depends on academic addiction medicine.